PENGETAHUAN REMAJA TERHADAP PERILAKU SEKS PRANIKAH PADA SISWA DI SMAN 6 PUNTEUT KOTA LHOKSEUMAWE - Elvieta, Elvieta; Us, Hafsah; AB, Myrna Lestari (NHM PRESS, 2024)
Premarital sexual behavior is a complex public health problem, influenced by various factors such as knowledge, social norms, and group pressure. It is hoped that sufficient knowledge about sex can influence a person's sexual behavior, but the relationship between the two still needs to be explored further. This study aims to test whether there is a significant relationship between knowledge about sex and pre-marital sexual behavior. This study used a cross-sectional design with a sample consisting of young adult individuals. Data was collected through a questionnaire that measured the respondent's level of sexual knowledge and pre-marital sexual behavior. Statistical analysis was carried out using a correlation test to determine the relationship between knowledge and behavior. The results of statistical tests show that there is no significant relationship between knowledge and pre-marital sexual behavior (p-value > 0.05). Even though respondents have sufficient knowledge about sex, factors other than knowledge, such as social pressure, group norms, and psychological and emotional aspects, influence their sexual behavior more. Sufficient knowledge about sex is not enough to be the main determining factor in changing premarital sexual behavior. These results indicate the need for a more complex approach in addressing the issue of pre-marital sexual behavior, involving social, psychological and emotional factors in addition to increasing knowledge